HUBUNGAN PEMANFAATAN SUMBER BELAJAR DAN KEMANDIRIAN BELAJAR DENGAN PRESTASI BELAJAR MAHASISWA PRODI D III KEBIDANAN KUSUMA HUSADA SURAKARTA - Rahajeng Putriningrum; Yunita Wulandari; Ratih Dwilestari Puji Utami (Universitas Kusuma Husada Surakarta, 2012)
ABSTRACT Based on case studies that researchers do in the Prodi DIII Midwifery Stikes Kusuma Husada Surakarta student achievement in all courses for the academic year 2010/2011 there are still many who have not graduated and do remidiasi in students who score less than the limit of graduation. Independence of learning are indispensable for the success of learning process, as well as the utilization of learning resources on campus are very supportive of students to achieve good performance. This becomes an evaluation for faculty to find the cause. This study aims to analyze the relationship utilization of learning resources and independence of learning with learning achievement in Prodi D III Midwifery Kusuma Husada Surakarta. This research is a quantitative analytical approach crossectional. Implementation research in Prodi D III Midwifery Kusuma Husada Surakarta. Sample of 140 female students who used the technique random disproportionate stratified sampling. The instrument used is the questionnaire. Analysis of data using corelasi product moment and multiple linear regression. The results of multiple linear regression in getting that student learning achievement Prodi DIII Midwifery Kusuma Husada Surakarta 40.8% influenced by the utilization of learning resources and learning independence, while the rest is influenced by other factors.. That there is a relationship utilization of learning resources and independence of learning with student learning achievement. Suggestions for institutional independence is expected to instill character study at universities in the scope of Prodi D III Midwifery kusuma Husada Surakarta.